1995
DOI: 10.1007/bf00169378
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in the density and subtype specificity of endothelin receptors in rabbit urinary tract

Abstract: We investigated the binding characteristics of endothelin (ET) receptors in rabbit ureter, bladder dome, bladder base, and urethra and compared the observed receptor properties with those of cloned human ETA and ETB receptors expressed in Chinese hamster ovary K-1 (CHO) cells. Receptor binding experiments with [125I]ET-1 revealed the presence of a single class of specific, saturable, high affinity [125I]ET-1 binding sites in all of the regions of the studied urinary tract. The rank order of the densities (Bmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
0
40
0
Order By: Relevance
“…The main role of ET A receptors in the contractile effects of ETs in the detrusor has been confirmed by several other investigators in animal as well as human bladders (Donoso et al, 1994;Latifpour et al, 1995;Okamoto-Koizumi et al, 1999;Calvert et al, 2002;Yoshida et al, 2003). In human detrusor, OkamotoKoizumi et al (1999), using isometric contraction experiments and RT-PCR, demonstrated that the ET-1-induced contractions were mediated mainly by the ET A receptor and not by the ET B receptor.…”
Section: Peripheral Targetsmentioning
confidence: 75%
“…The main role of ET A receptors in the contractile effects of ETs in the detrusor has been confirmed by several other investigators in animal as well as human bladders (Donoso et al, 1994;Latifpour et al, 1995;Okamoto-Koizumi et al, 1999;Calvert et al, 2002;Yoshida et al, 2003). In human detrusor, OkamotoKoizumi et al (1999), using isometric contraction experiments and RT-PCR, demonstrated that the ET-1-induced contractions were mediated mainly by the ET A receptor and not by the ET B receptor.…”
Section: Peripheral Targetsmentioning
confidence: 75%
“…300 nM BQ 123, and 30 nM STXc. These concentrations of BQ 123 and STXc, which are approximately 100 times greater than that of their high-affinity constants, K iH , (Latifpour et al 1995) occupy virtually all of the endothelin ETA and ETB receptor subtypes, respectively, in the rat adrenal sections.…”
Section: Autoradiographymentioning
confidence: 86%
“…The membrane particulates from adrenal glands were prepared as described previously (Latifpour et al 1995, Saito et al 2000a. In brief, the adrenal specimens were homogenized on ice in 20 mM Hepes (pH 7·4) containing 100 mM NaCl, 3 mM EDTA, 1 mM EGTA and the following protease inhibitors: 0·1 mM phenyl methyl sulfonyl fluoride and 10 µg/ml each of aprotinin, leupeptin, pepstatin A, and soybean trypsin inhibitor.…”
Section: Preparation Of Adrenal Membrane Particulatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the urinary tract, several investigators have investigated the physiological effects of ET and ET receptors using pharmacological, histochemical and receptor binding technique both in bladder [13][14][15][16][17][18][19][20][21][22] and prostate [23][24][25][26]. ET receptors have been shown to mediate contraction of isolated human bladder tissue strips [19][20][21].…”
Section: Introductionmentioning
confidence: 99%